Analisis sistem pemeliharaan taman studi kasus The Blooms Garden Bali - Anak Agung Keswari Krisnandika; I Gusti Ngurah Agung Wahyu Mulyanugraha; I Made Agus Dharmadiatmika (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Garden maintenance is an important aspect for maintain the beauty and comfort of a garden. The maintenance aims to make sure the garden always in accordance with the orginal design intent, especially by maintaining the plants conditions. The Blooms Garden Bali is a thematic flowering garden for tourist attractions. This tourist object is located in Banjar Batusesa, Candikuning Village, Baturiti District, Tabanan Regency, Bali Province. This study aims to analyze the maintenance system implemented by The Blooms Garden Bali. The method used in this study are observation, interviews, and literature study with the research stages including preparation, inventory, analysis and synthesis, as well as identification of garden maintenance. The research results show that the maintenance system used is unit maintenance in the form of division into several maintenance zones and special maintenance related to maintenance that requires special skills. The maintenance concept applied is ideal maintenance, namely maintenance that refers to the initial concept and physical maintenance in the form of sweeping, watering, pruning, fertilizing, embroidering and hardscape maintenance.